EFFECT OF SOME PLANT EXTRCT, CALICUM CHLORIDE AND STORAGE METHOD IN QUALITIES AND MARKETING OF THE APRICOT FRUITS, 3ZAGAINAA (2) PHYSICAL CHARACTERISTICS. - Burhan, Marwa Hadi; AL-Shemmery , Ghalib Naser (Diyala Agricultural Sciences Journal, 2013)
The study was conducted in the laboratory of Department of Horticulture and Landscape on the fruits of apricot class (Zagainah 3). The fruits stored at refrigerated store's and evaporative In the store of the Department of Horticulture ,College of Agriculture -Tikrit University for two seasons, 2008 – 2009 .Fruits Taken from a 7-yearold trees from a private orchard near the city of Baiji ,3/4 fruits coller after 79 days afterfull plum at 20/5 ,22/5/ 2009. Fruits dupping in axctract, Okra 75% consitration 20 mintis,pomogranatium 8%con. 5mints,Sider leaves75% con.20 mints andCalicumCloraid 5% con. The control treatment of fruits difided tow parts, the first storage at coold storage at 4 o ±1o and 80-85% temperature, anther storage at ventilation storage. The fruitspackeg at poleyethelen 5kg. Yoused C.R.D in analysis. The Resilt. 1- CalicumCloriddecres, Waite lose, dacy, respiration. 2-fruits treatment with Okra extract decreas fruits respiration to 16.8 mg/kg/hr in cold storage and 17.2 mg/kg/hrjnventelation storage. 3- Pomegranate peel extract significantwaight loss, dacyeand respiration. 4- Sider leaves extracts loss in whaiteloss respiration and private micrnic infected. 5- Control treatment wheightloss,dacey and respiration rate